Production of oil with increasing palmitoleic acid content by Cyberlindnera subsufficiens NG8.2 from oil palm empty fruit bunch via co-fermentation with cassava starch - Weeraphan, Trinset; Savarajara, Ancharida (Agriculture and Natural Resources, 2022)
Palmitoleic acid is a monounsaturated fatty acid that has been shown to have many important health benefits, with broad applications in medicines and cosmetics. Intracellular oils accumulated in yeast cells are mostly in the form of triacylglycerols, of which some are contain palmitoleic acid. This work investigated oil palm empty fruit bunch (OPEFB) as a potential feedstock for the production of oils with a high palmitoleic acid content using Cyberlindnera subsufficiens NG8.2. The low sugar concentration of the OPEFB hydrolysate (OPEFBH) was overcome by the co-utilization of cassava starch hydrolysate (CSH). The maximum oil titer of Cy. subsufficiens NG8.2 at 30°C was almost the same in a mixture of either OPEFBH plus CSH (OPEFBH-CSH) or OPEFBH plus glucose (OPEFBH-G) at the same final glucose concentration (50 g/L). However, the oil produced using OPEFBH-CSH contained a higher palmitoleic acid content (18.51% weight per weight, w/w) than from OPEFBH-G (10.41%, w/w). Supplementation of OPEFBH-CSH with 1 g/L KH2PO4, 0.05 g/L MgSO4∙7H2O and 0.01 g/L CaCl2∙2H2O (pH 5.0) increased the oil titer from 1.17 g/L to 1.96 g/L. Reducing the incubation temperature from 30°C to 25°C increased the palmitoleic acid content from 18.03% (w/w) to 21.49% (w/w) without any significant effects on the oil titer and oil composition.